2018
DOI: 10.1007/978-3-030-00671-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Erroneous Identity Links on the Web Using Network Metrics

Abstract: In the absence of a central naming authority on the Semantic Web, it is common for different datasets to refer to the same thing by different IRIs. Whenever multiple names are used to denote the same thing, owl:sameAs statements are needed in order to link the data and foster reuse. Studies that date back as far as 2009, have observed that the owl:sameAs property is sometimes used incorrectly. In this paper, we show how network metrics such as the community structure of the owl:sameAs graph can be used in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 23 publications
0
34
0
3
Order By: Relevance
“…Thus, if two aligned movies violate these patterns, then they are more likely to be wrong. Existing approaches to detect invalid owl:sameAs can be used in this context …”
Section: Problem Statement: Immentioning
confidence: 99%
“…Thus, if two aligned movies violate these patterns, then they are more likely to be wrong. Existing approaches to detect invalid owl:sameAs can be used in this context …”
Section: Problem Statement: Immentioning
confidence: 99%
“…This class, which in theory should include instances referring to the same real-world entity, contains in practice around 177K instances referring to various countries, cities, people, and religions. In this context, a recent approach [17,18] tried to limit the eects of such erroneous statements by assigning an error degree to each of these 558M owl:sameAs statements in sameAs.cc, based on the community structure of the owl:sameAs network. These error degrees will be used in this study as indicators of the quality of owl:sameAs links.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, by randomly generating 416K alignments between 833K concepts, we showed that considering all owl:sameAs links increases the Jaccard index of 94 randomly aligned pair of concepts (0.02% of the cases). Following a number of studies showing that owl:sameAs is misused in the Web of data [8,10,17], we investigate in this section whether selecting a subset of these owl:sameAs links, of higher…”
Section: Does the Quality Of Owl:sameas Links Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Dans cet article, qui est une version étendue de (Raad et al, 2018), nous présentons une nouvelle approche pour la détection automatique de liens owl:sameAs potentiellement erronés, qui n'utilise aucune hypothèse sur les données ou sur le schéma. L'approche consiste en l'application d'un algorithme de détection de communautés dans les graphes RDF réduits aux assertions de liens owl:sameAs.…”
Section: Introductionunclassified